2021
DOI: 10.5812/gct.108995
|View full text |Cite
|
Sign up to set email alerts
|

Anti-cancer Effects of Pomegranate Seed Oil on Esophageal Cancer Cell Line (KYSE-30)

Abstract: Background: Esophageal cancer is the eighth most common cancer and the sixth most frequent cancer-related death. Despite improvements in treatment approaches, it has remained one of the most challenging cancers for treatment. Thus, it is necessary to introduce novel and efficient methods for treatment. In this regard, the anti-cancer and antioxidant properties of pomegranate have been more concerned. Objectives: The present study aimed to assess the potential cytotoxicity effects of pomegranate on the esophage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 42 publications
(48 reference statements)
0
4
0
Order By: Relevance
“…Some authors preserve the idea that functional foods should be classified only by their preventive character instead of its medicinal potential [21,22]. Pomegranate, considered a functional fruit for its antioxidant capacity, also demonstrates a medicinal role against many non-communicable diseases like diabetes [23] and cancer [24]. The assessment of PPE antioxidant activity assayed by DPPH assay, where the DPPH odd electron of nitrogen atom is reduced by receiving a hydrogen atom from the tested antioxidants, demonstrated that PPE has an effective antioxidant activity as reflected by the inhibition of the free radical DPPH (80.4 ± 0.90).…”
Section: Discussionmentioning
confidence: 99%
“…Some authors preserve the idea that functional foods should be classified only by their preventive character instead of its medicinal potential [21,22]. Pomegranate, considered a functional fruit for its antioxidant capacity, also demonstrates a medicinal role against many non-communicable diseases like diabetes [23] and cancer [24]. The assessment of PPE antioxidant activity assayed by DPPH assay, where the DPPH odd electron of nitrogen atom is reduced by receiving a hydrogen atom from the tested antioxidants, demonstrated that PPE has an effective antioxidant activity as reflected by the inhibition of the free radical DPPH (80.4 ± 0.90).…”
Section: Discussionmentioning
confidence: 99%
“…Intriguingly, pomegranate peel dietary intake reduces total chromosomal aberrations and aberrant metaphase frequencies of barium-treated rats ( Elwej et al, 2016 ). MTT assay showed the cytotoxicity and antiproliferation effect of the pomegranate seed oil in esophageal, breast, and ovarian cancer cell lines ( Shirode et al, 2014 ; Seidi et al, 2016 ; Zare et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…The anti-breast cancer properties of pomegranate extract could partially depend upon the targeting of microRNAs [33,34] . Pomegranate Seed Oil (PSO) has prevented different types of tumor cell proliferation [34] .…”
Section: : Biochemical Components Of Pomegranate and Its Main Anti-br...mentioning
confidence: 99%